Quo Vadis: Technology Transfer Regulation in the IPR System in Indonesia - Puti Mayang Seruni (Jurnal Ilmiah Dunia Hukum, 2025)
This article aims to examine how the current regulation of technology transfer in Indonesia, especially in relation to the IPR regime, and its relevance to Indonesia's development. Adoption and application of science and technology, as one of the keys in implementing the vision of a Golden Indonesia in 2024, can be achieved through technology transfer. To achieve this, it is necessary to have regulations that require foreign companies to transfer technology to the host because the success of technology transfer depends on the regulations of the host country. The problem addressed in this study is that the 2023 Job Creation Law actually eliminates the obligation to transfer technology as stipulated in Article 20, paragraph 2 of the Patent Law. Using a normative legal research approach, this study looks at secondary data from primary, secondary, and tertiary legal materials that are pertinent to the issue. The results of the discussion show that technology transfer, IPR, and development are closely related. Technology transfer as a means to gain access to science and technology that is protected by IPR. IPR is fundamental for a nation because economic progress can be seen from the acquisition of intellectual property owned by the nation. The richer the intellectual property, the faster the nation's economic growth. Government intervention in technology transfer is essential for economic development and welfare in Indonesia. Therefore, the obligation of technology transfer must be regulated in several laws and regulations, especially in the Job Creation Law and Patent Law.